The Historiography of the Greek Revolution of 1821: From Memoirs to National Scholarly History, 1821–1922 - Stathis, Panagiotis (Historein, 2021)
This study discusses the historiography of the Greek Revolution of 1821, what in Greek is often referred to as “Twenty-One” (Eikosiena) or the “Struggle” (Agon). Since 1821 constitutes the founding condition of the Greek state and autonomous existence of the Greek nation, it can be considered as the main historiographical field of modern Greek history. Throughout most of the twentieth century it represented a field of conflict between opposing historiographical but also ideological and political currents. Opposing ideological environments and collective identities formed different readings of Greek history in which the Greek Revolution played a central role. Its reading and interpretation served as the compass for reading and interpreting the whole process of modern Greek historical development. Opposing collectives also made selective use of the history of 1821 by searching for their “ancestors” in the revolutionary past; thus they formed historical genealogies through which they could claim authentic continuity with leading social groups and figures of the revolution. Consequently, 1821 obtained exemplary power. Accordingly each of its readings functioned as the starting point in shaping the political practice in the present. In other words, each and every reading of 1821 formed or supported directional guides of political practices in the present.